Countercurrent enzymatic saccharification of cellulosic biomass. (July 2016) - Zentay, Agustin N.; Liang, Chao; Lonkar, Sagar; Holtzapple, Mark T.
Abstract: At pH 4.8 and 50 °C, semi-continuous countercurrent saccharification was performed using α-cellulose. Every second day, solids and liquids were transferred countercurrently and liquid samples were taken to determine sugar concentration in each stage. Train 1 (5 mg protein/g biomass, 8 stages) achieved 87.8% glucose conversion and 102 g/L total sugar. Train 2 (2 mg/g, 8 stages) achieved 56.1% glucose conversion and 65 g/L total sugar. Train 3 (2 mg/g, 16 bottles) achieved 73.6% glucose conversion and 67 g/L total sugar. Compared to 5-day batch saccharification, to achieve the same glucose conversion, enzyme requirements were reduced by factors of 16.8, 8, and 20.5 for Trains 1, 2, and 3, respectively. Further improvements can be realized by changing the enzyme addition point and increasing the number of stages. Highlights: Countercurrent saccharification of cellulosic biomass was investigated. HPLC was used to quantify sugar concentrations in liquid samples. Countercurrent operation shows significant gains over batch operation. Achieved high conversion and high sugar concentration at very low enzyme loading. Potential for further improvements in operation and biomass pretreatment.